(untitled) (Context: Journal of Interdisciplinary Studies, 2024)
The family factor (i.e., parenting style) is among the most important factors affecting adolescents’ development, in particular their mental health. This study investigates the relationship between perceived parenting styles and mental health among adolescents, through the mediating effects of gender, age, child order, family type, income and religious attachment. It then quantitatively evaluates perceptions regarding the prevalence of mental health disorders among adolescents in seven Albanian community secondary schools in North Macedonia’s capital, Skopje. The results showed that authoritative parenting was the most common perceived style, followed by authoritarian and permissive parenting, and that mental health among adolescents was generally poor. Further, correlations were found between different parenting styles and particular aspects of mental health among Albanian adolescents in North Macedonia. It is hoped that the findings of this study will provide targeted guidance for the prevention of adolescent mental health problems.